Katolicka nauka społeczna – aktualne wyzwania - Mazurkiewicz, Piotr (Społeczeństwo, 2022)
Nowadays, the main task of the Catholic social teaching has not been focused on finding specific answers for the „retail” problems of the world. It also has not been devoted to challenge social teachings in order to find the most efficient „technology” to make the world a better place. Lecturers of the Catholic social teaching must not feel embarrassed when they lose in the race for gatherers of aluminum and other waste or when they are unable to come up with solutions concerning, e.g. a better party system. However, they should not allow having the meaning of Catholic social teaching be reduced to the role of a merchant offering hope for temporal salvation. The essential challenge is to analyze the world and ensure that the Church will not acquire a paradigm that is contrary to the Christian paradigm. The Church has actually something to be communicated to the world only when one crucial matter is properly established, i.e. the awareness that people and the mankind are moving „from God to God”, from creation to eternal salvation. When people look at the world from the proper perspective, the Church might help them make it a better place.